From Loren to Marimar the Philippines media in the 1990's - Coronel, Sheila S. (Philippine Center for Investigative Journalism, 1999)
An anthology of 35 PCIJ articles first published in various newspapers. The book traces how, in just a decade, the media in the Philippines got to be as powerful as it is now. It also examines the structure of Philippine newspapers and television, describes Filipino forays into the World Wide Web, and probes such problems as ethics and ownership.